PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN GOOGLE MEET DENGAN ZOOM MEETING PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 18 PALEMBANG - Yolanda Permata Sari; Zahruddin Hodsay; Januardi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
This study aims to determine the compararison of student learning outcomes using google meet with zoom meeting on economics class XI social studies at SMA Negeri 18 Palembang. The population of this study were all students of class XI IPS SMA Negeri 18 Palembang, totaling 100 students. The sample of this study amounted to 67 students consisting of class XI IPS 1 who used google meet and class XI IPS 2 which used zoom meeting. The method used in this research is a comparative method.The collection of test data was analyzed with averages and then hypothesis testing was carried out using the t-test. Based on the results of the research and discussion, it can be concluded that there is a comparison of student learning outcomes using google meet with zoom meetings on economics class XI social studies at SMA Negeri 18 Palembang. The result of hypothesis testing shows that tcount > ttabel or 14,892 > 1,997 can be concluded that Ho is rejected and Ha is accepted or there is a comparison of student learning outcomes using google meet with zoom meeting on economics class XI social studies at SMA Negeri 18 Palembang.